How did rivers in the wet tropics (NE Queensland, Australia) respond to climate changes over the past 30 000 years?. (31st May 2017) - Hughes, Kate; Croke, Jacky
ABSTRACT: The nature and timing of fluvial response and coincident changes in climate as inferred from multiple, independent proxies are examined in the wet tropics of north‐eastern Australia. Chronostratigraphic data provide evidence for regionally synchronous fluvial aggradation at 30–13 ka, 8–5 ka and again from 1 ka. Terrace incision and removal occurred at 13–8 ka and 5–1 ka. A new synthesis of regional palaeoenvironmental proxy records spanning the last 30 ka highlights key periods of environmental change. Comparison of the records of fluvial and environmental change reveals the relationship is complex with no clear relationship between river aggradation/incision and wetter/drier conditions. The nature and timing of fluvial response in the wet tropics also shows broad similarities with coastal valleys in south‐eastern New South Wales, suggesting continental‐scale controls on fluvial response to changing climate during the Late Quaternary in Australia. Copyright © 2017 John Wiley & Sons, Ltd.